Animal models in biomedical research: Relevance of Drosophila melanogaster - Olabisi Tajudeen Obafemi; Ademola Olabode Ayeleso; Olusola Bolaji Adewale; Jeremiah Unuofin; Bidemi Emmanuel Ekundayo; Monde Ntwasa; Sogolo Lucky Lebelo (Heliyon)
Animal models have become veritable tools in gaining insight into the pathogenesis and progression of several human diseases. These models could range in complexity from Caenorhabditis elegans to non-human primates. With the aid of these animal models, a lot of new knowledge has been gained about several diseases which otherwise would not have been possible. Most times, the utilization of these animal models is predicated on the level of homology they share with humans, which suggests that outcomes of studies using them could be extrapolated to humans. However, this has not always been the case. Drosophila melanogaster is becoming increasingly relevant as preferred model for understanding the biochemical basis of several human diseases. Apart from its relatively short lifespan, high fecundity and ease of rearing, the simplicity of its genome and lower redundancy of its genes when compared with vertebrate models, as well as availability of genetic tool kit for easy manipulation of its genome, have all contributed to its emergence as a valid animal model of human diseases. This review aimed at highlighting the contributions of selected animal models in biomedical research with a focus on the relevance of Drosophila melanogaster in understanding the biochemical basis of some diseases that have continued to plague mankind.